ENHANCING STUDENTS SCIENCE COMMUNICATION SKILLS THROUGH MORE LEARNING MODEL - Taufanny Putri Pratiwi; Munasir Munasir; Nadi Suprapto (Universitas Negeri Surabaya, 2020)
A This study aims to analyze students science communication skills in the physics learning process especially in the Work and Energy concept using (Model-Observe-Reflect-Explain) MORE learning models. The research used a mixed method by utilizing test, questionnaires, and interviews with 10th and 11st grade students majoring in science, physics teachers and headmaster. The data was obtained by taking the physics scores of students in the work and energy concept who have received learning with the MORE learning model, then provides a questionnaire containing the obstacles faced by students in learning physics and interviews with students and teachers regarding learning constraints and science communication skills after learning using the MORE learning model. The findings indicated the MORE learning model helps students in practising science communication skills in learning with good student science communication skills will increase students understanding of Work and Energy concepts as seen from the students scores in the work and energy concept. Keywords: science communication skill, MORE learning model, mixed methods, physics, cognitive ability Abstrak Penelitian ini bertujuan untuk menganalisis keterampilan komunikasi sains siswa dalam proses pembelajaran fisika khususnya pada materi pembelajaran Usaha dan Energi dengan menggunakan model pembelajaran (Model-Observe-Reflect-Explain) MORE. Penelitian ini menggunakan mixed method dengan menggunakan tes, angket, dan wawancara yang diberikan pada siswa kelas 10 dan 11 jurusan IPA, guru-guru fisika dan kepala sekolah. Pengumpulan data dilakukan dengan cara mengambil nilai fisika siswa yang telah mendapatkan pembelajaran pada materi Usaha dan Energi dengan model pembelajaran MORE, kemudian memberikan angket yang diisikan kendala-kendala yang dihadapi siswa selama proses pembelajaran fisika dan wawancara dengan siswa dan guru mengenai kendala-kendala selama proses pembelajaran untuk melatihkan keterampilan komunikasi sains dengan menggunakan model pembelajaran MORE. Hasil penelitian yang diperoleh, menunjukkan bahwa model pembelajaran MORE dapat membantu siswa dalam melatihkan keterampilan komunikasi sains dalam pembelajaran fisika. Meningkatnya keterampilan komunikasi sains siswa maka akan meningkatkan pula pemahaman siswa pada materi Usaha dan Energi yang terlihat dari nilai yang diperoleh siswa. Kata Kunci: keterampilan komunikasi sains, model pembelajaran MORE, mixed methods, fisika, kemampuan kognitif